Treatment Outcomes of High-Risk Non-Muscle Invasive Bladder Cancer (HR-NMIBC) in Real-World Evidence (RWE) Studies: Systematic Literature Review (SLR) - Musat MG; Kwon CS; Masters E; Sikirica S; Pijush DB; Forsythe A (Dove Medical Press, 2022)
Mihaela Georgiana Musat,1 Christina Soeun Kwon,1 Elizabeth Masters,2 Slaven Sikirica,3 Debduth B Pijush,3 Anna Forsythe4 1Evidence Generation, Purple Squirrel Economics, a Wholly Owned Subsidiary of Cytel, Inc., Waltham, MA, USA; 2Real World Evidence, Pfizer, New York, NY, USA; 3Global Health Economics and Outcomes Research, Pfizer, New York, NY, USA; 4Value and Access, Purple Squirrel Economics, a Wholly Owned Subsidiary of Cytel, Inc., Waltham, MA, USACorrespondence: Mihaela Georgiana MusatPurple Squirrel Economics, a Wholly Owned Subsidiary of Cytel, Inc, 1050 Winter Street, Waltham, MA, 02451, USAEmail mihaela.musat@pshta.comBackground: To date, there has been limited synthesis of RWE studies in high-risk non-muscle invasive bladder cancer (HR-NMIBC). The objective of this research was to conduct a systematic review of published real-world evidence to better understand the real-world burden and treatment patterns in HR-NMIBC.Methods: An SLR was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines with the scope defined by the Population, Intervention Comparators, Outcomes, and Study design (PICOS) criteria. EMBASE, MEDLINE, and Cochrane databases (Jan 2015-Jul 2020) were searched, and relevant congress abstracts (Jan 2018-Jul 2020) identified. The final analysis only included studies that enrolled ≥ 100 patients with HR-NMIBC from the US, Europe, Canada, and Australia.Results: The SLR identified 634 RWE publications in NMIBC, of which 160 studies reported data in HR-NMIBC. The average age of patients in the studies was 71 years, and 79% were males. The rates of BCG intravesical instillations ranged from 3% to 86% (29- 95% for induction and 8- 83% for maintenance treatment). Five-year outcomes were 17- 89% recurrence-free survival (longest survival in patients completing BCG maintenance), 58- 89% progression-free survival, 71- 96% cancer-specific survival (lowest survival in BCG-unresponsive patients), and 28- 90% overall survival (lowest survival in patients who did not receive BCG or instillation therapy).Conclusion: BCG treatment rates and survival outcomes in patients with HR-NMIBC vary in the real world, with better survival seen in patients completing maintenance BCG, responding to treatment, and not progressing to muscle-invasive disease. There is a need to better understand the factors associated with BCG use and discontinuation and for an effective treatment that improves outcomes in HR-NMIBC. Generalization of these results is limited by variations in data collection, reporting, and methodologies used across RWE studies.Keywords: real-world outcomes, high-risk NMIBC